PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA PENGGELAPAN DALAM PUTUSAN NOMOR 4/PID.B/2023/PN YYK - Debrio Daffa Abroor; Dara Puspita Sukma (Sebelas Maret University, 2025)
This article analyses criminal procedure law related to the suitability of the judge's consideration in deciding the criminal case of fraud in position in Verdict Number 4/Pid.B/2023/PN Yyk with the provision of Article 183 of the Criminal Procedure Code. The purpose of this article is to determine whether the judge's consideration in deciding the criminal case of fraud in position in Verdict Number 4/Pid.B/2023/PN Yyk is in accordance with the provision of Article 183 of the Criminal Procedure Code. This research is a normative legal research or doctrinal legal research that is prescriptive and applied. Types of legal materials used are primary legal materials and secondary legal materials. The technique used in collecting legal materials is document study or literature study. The finding proves that the judge's consideration of rendering a 3 (three) years prison sentence in case of fraud in position in Verdict Number 4/Pid.B/2023/PN Yyk has been in accordance with the provision of Article 183 of the Criminal Procedure Code.